Influence of Lewis acid charge and proximity in MoMo⋯M linear chain compounds with M = Na+, Ca2+, Sr2+, and Y3+. (8th January 2016) - Dolinar, Brian S.; Berry, John F.
Graphical abstract: The syntheses, X-ray structural characterizations, and electrochemical properties of four new paddlewheel [MMo2 (SNO5)4 Cl] n −1+ (M n +  = Na +, Ca 2+, Sr 2+, Y 3+ ; HSNO5 = monothiosuccinimide) compounds are described here. By changing the M n + cation charge density, the Lewis acidity of the MoMo quadruple bond and the [Mo2 ] 4+/5+ redox potential are tuned. Abstract: The syntheses, X-ray structural characterizations, and electrochemical properties of four new paddlewheel [MMo2 (SNO5)4 Cl] ( n −1)+ (M n +  = Na +, Ca 2+, Sr 2+, Y 3+ ; HSNO5 = monothiosuccinimide) compounds are described here. By changing the M n + cation charge and size, we demonstrate a method for easily tuning the Lewis acidity of the MoMo quadruple bond and the [Mo2 ] 4+/5+ redox potential. As the charge of the M n + cation is increased, the distal Mo atom becomes more Lewis acidic, leading to a shorter Mo2 –Cl bond distance, and the [Mo2 ] 4+/5+ redox couple becomes less accessible. As the M n + ⋯Mo2 distance is increased, the distal Mo atom becomes less Lewis acidic, leading to a longer Mo2 –Cl bond distance.